Non-Specific Immune Potentiating activity of Multivitamins in Catfish (Clarias sp.) - Cahyono Purbomartono; Ulfatun Rizkiyah; Dini Siswani Mulia; Arief Husin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2021)
Fish farming is well developed because many people like to consume fish. The main problem in cultivation is an attack of a disease. Generally, the disease in fish is MAS (Motile Aeromonas Septicemia) which is caused by Aeromonas hydrophila. Prevention of diseases in fish can be done by increasing immunity through the addition of multivitamins in feed. This study aims to determine the ability of multivitamins against non-specific immune responses in African catfish (C. gariepinus) as well as to know the optimum dose. The study used an experimental method with a completely randomized design using 3 treatments, 1 control, and 4 individual replications. The treatment using a multivitamin through feed with a dose of T1 = 2 g kg-1, T2 = 2.5 g kg-1, T3 = 3 g kg-1 and T0 = control. The parameters observed were phagocytic activity, and differential leukocytes of monocytes and lymphocytes. Data were analyzed using Analysis of variance (ANOVA) at the 95% confidence level. If there is a real difference, then proceed with the Duncan Multiple Range test Test (DMRT) at a 95% confidence level. The results showed that the addition of multivitamins through feed on African catfish had a significant effect (p<0.05) on phagocytic activity and differential leukocyte of monocytes, but had no significant effect (p> 0.05) on differential leucocytes of lymphocyte. The optimum dose for increasing non-specific immune responses in African catfish is T2 at a dose of 2.5 g kg-1 of feed. Based on research, the addition of multivitamins through the feed can potentially be used in fish farming to increase immunity.